Beyond the Condom: Frontiers in Male Contraception - Roth, Mara Y.; Amory, John K. (Seminars in Reproductive Medicine, 2016)
Nearly half of all pregnancies worldwide are unplanned, despite numerous contraceptive options available. No new contraceptive method has been developed for men since the invention of condom. Nevertheless, more than 25% of contraception worldwide relies on male methods. Therefore, novel effective methods of male contraception are of interest. Herein we review the physiologic basis for both male hormonal and nonhormonal methods of contraception. We review the history of male hormonal contraception development, current hormonal agents in development, as well as the potential risks and benefits of male hormonal contraception options for men. Nonhormonal methods reviewed will include both pharmacological and mechanical approaches in development, with specific focus on methods which inhibit the testicular retinoic acid synthesis and action. Multiple hormonal and nonhormonal methods of male contraception are in the drug development pathway, with the hope that a reversible, reliable, safe method of male contraception will be available to couples in the not too distant future.
Keywords: testosterone; retinoic acid; contraception; spermatogenesis